Manifestations of immunoglobulin G4 related disease in otolaryngology: case reports and review of the literature. Issue 2 (27th June 2014) - Wong, W K; Campbell, R; Douglas, R
Abstract Background: Immunoglobulin G4 related disease is an inflammatory condition characterised by the presence of fibrotic lesions infiltrated by immunoglobulin G4 positive plasma cells. It can arise from almost any region of the body and it is being increasingly recognised in the head and neck. Regardless of the site of involvement, the histopathological resemblance is remarkable. Dense lymphoplasmacytic infiltration, overabundance of immunoglobulin G4 bearing plasma cells and presence of storiform fibrosis are typical findings. Case reports: This paper presents two cases of immunoglobulin G4 related disease in which there was involvement of the orbit, the infraorbital nerve and the infratemporal fossa. Diagnosis was established in both cases by biopsying radiologically abnormal tissue in the infratemporal fossa. Conclusion: An awareness of this condition is required to establish the diagnosis and initiate appropriate therapy. Glucocorticoids are the mainstay of initial treatment. The effectiveness of B-lymphocyte depletion with rituximab has also been reported. Correct diagnosis may spare patients from unnecessarily radical surgery.